Introduction to the Special Issue - Faith E. Crampton; David C. Thompson; R. Craig Wood (Educational Considerations, 2013)
We are pleased to bring you the second of two special issues of Educational Considerations comprised of papers presented at the 2012 National Education Finance Conference in San Antonio, Texas.
Keywords: National Education Finance Conference